Missione compiuta. Sul senso politico dell’omicidio Moro - Vander, Fabio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2026)
This analysis argues that the political strategies of Aldo Moro and Enrico Berlinguer—the "Historic Compromise" and Moro's "Third Phase"—were intrinsically flawed, creating an aporia that perpetuated Italy's "blocked democracy." By seeking to overcome political stalemate through a grand coalition of traditionally opposed parties (DC and PCI), they inadvertently reinforced the system's imperfections. This critical failure, the text contends, created the conditions that made terrorist violence—specifically the kidnapping and murder of Aldo Moro—seem like a "necessary" means to force a political transformation. The ultimate, tragic success of the terrorists was not in achieving revolution, but in definitively closing the Moro-Berlinguer era, leading to the subsequent political landscape shaped by the very forces that orchestrated the crisis. The murder of Moro was thus a "perfect crime" that achieved its strategic goal of destabilizing to stabilize. Aldo Moro; Historic Compromise; Blocked Democracy; Political Terrorism; Strategy of Tension.